Evaluation of the quality of fermented kiwi wines made from different kiwifruit cultivars. (August 2021) - Huang, Jintao; Li, Hongcai; Wang, Yaqin; Wang, Xingnan; Ren, Yichen; Yue, Tianli; Gao, Zhenpeng
Abstract: This study evaluated the physicochemical properties of the juices of different kiwi cultivars before and after fermentation. The organic acid, monomeric phenol, aroma, and alcohol contents of seven kiwi wines were analyzed. The results revealed that Guichang wine had the highest total phenol content and the highest principal component analysis score. Xuxiang wine had the highest organic acid, quinic, and lactic acid contents, while Jinkui wine had the highest acetic, citric, and malic acid contents. The main monomeric phenols present in kiwi wine were protocatechuic, ellagic, and gallic acids. Guichang wine had the highest gallic acid content, while Hayward wine had the highest protocatechuic and ellagic acid contents. Furthermore, Guichang wine had the highest volatile aroma content, while Miliang One wine had the most aromatic compounds (n = 45) in volatile aromas. Miliang One wine had the highest alcohol content and Jinkui wine had the lowest. Highlights: Guichang wine had the highest principal component analysis score. Citric, lactic, and quinic acids were the most abundant organic acids in the wines. Notably, the quercetin content in Guichang wine was higher than that in the other wines. Guichang wine had the highest, and Jinkui wine the lowest, total volatile aroma content. The Miliang One and Jinkui wines had the highest and lowest alcohol contents.